Profissionalização do magistério na educação básica: análise da valorização profissional do professor da educação infantil e anos iniciais do ensino fundamental - Custódio, Maria do Carmo (2011)
This research aims to understand and analyze the implications of educational policies for improving the teaching, post LDB 9394/96, in the process of professionalization of teaching in basic education, especially in kindergarten and early years of elementary school. Considering the professional differences between teachers in initial and final stages of basic education, research is directed toward the analysis of teacher s professional development of kindergarten and early years of elementary school in the municipal schools of Uberaba-MG. Like a conceptual cutout, the study focuses on two axes of discussion and analysis: first, the theoretical debate on the issues related to teaching and professionalization of teaching, and second, the management of public policies aimed at valorization of teaching in the context of the educational reforms arising from the LDB 9394/96, focusing fundamentally training and career. These axes allow us to think the complexity of links and interpenetrations within the process of professionalization of faculty teaching, the tension between public policy of valorization of teaching, when taking the dimensions of training and career as a unit and the implications for the teacher s professional valorization in kindergarten and early years of elementary school. This is a qualitative research with a descriptive and exploratory mold, with the principles of Freire's epistemology dialectic. For the survey, was used as procedures: a bibliographical and documentary research, application of questionnaires and semistructured interviews. For the research of lifting of empiric data were investigated educational managers and teachers working in kindergarten and early years of elementary schools of the municipal school of Uberaba-MG. This study allowed us to realize that policies for valorization of teaching, in those matters which relate to training and career are historically intertwined with the problem of quality of public education. With regard to the teaching profession, we can see a split between those who possess knowledge or not a socially recognized knowledge. In this sense, teaching in kindergarten and early years of primary education is still not recognized as a profession by society and governments in its training and career policies. The discourse of professionalism has been constituted as a contradictory set of values in the articulation of production and reproduction that has served to maintain the devaluation of the teaching profession and to legitimize the control and the reforms sought by the State. Thus, the discourse of the professionalization of the educational policies converges in practices against the professionalization